Study of the pyrolysis process of household polymer waste - Lebedev, Vladimir; Kopylov, Serhii; Rudneva, Kateryna; Miroshnichenko, Denis Viktorovich; Cherkashyna, Anna; Miroshnychenko, Mykhailo (Національний технічний університет "Харківський політехнічний інститут", 2025)
Abstract The research aims to study the functional and monomer composition of the obtained samples of pyrolysis products from the most common household polymer waste to determine the possibility of their use in industrial technologies using chromatography. The analysis of modern methods for recycling household polymer waste allows us to establish that one of the promising methods is their thermochemical decomposition (destruction) by pyrolysis. It has been shown that in the process of pyrolysis of a mixture of polymer waste, plastic waste decomposes into liquid and gaseous fractions with the release of a solid residue, the amount of which depends on the degree of contamination of the waste and the type of plastic. It has been established that the main part of plastic waste includes products of thermal destruction of polyethene, polypropylene and polyethene terephthalate and they are 90-95% represented by unbranched alkanes and alkenes.
Keywords: pyrolysis; household polymer waste; products; chromatography; research